Healthy Volunteers' Perceptions of the Benefits of Their Participation in Phase I Clinical Trials. (December 2018) - Fisher, Jill A.; McManus, Lisa; Wood, Megan M.; Cottingham, Marci D.; Kalbaugh, Julianne M.; Monahan, Torin; Walker, Rebecca L.
Other than the financial motivations for enrolling in Phase I trials, research on how healthy volunteers perceive the benefits of their trial participation is scant. Using qualitative interviews conducted with 178 U.S. healthy volunteers enrolled in Phase I trials, we investigated how participants described the benefits of their study involvement, including, but not limited to, the financial compensation, and we analyzed how these perceptions varied based on participants' sociodemographic characteristics and clinical trial history. We found that participants detailed economic, societal, and noneconomic personal benefits. We also found differences in participants' perceived benefits based on gender, age, ethnicity, educational attainment, employment status, and number of clinical trials completed. Our study indicates that many healthy volunteers believe they gain more than just the financial compensation when they accept the risks of Phase I participation.